La actividad minero-metalúrgica del Cu, Zn, Pb y su influencia en el crecimiento económico del Perú, 1996-2018 - Ospino Edery, Juan José Manuel Ysaac (2021)
For more than a century, the main economic activity in our country has been metallurgical mining, being in the last three decades mostly managed by foreign companies, limiting the role of the state to promoting investments in a non-renewable resource, abundant and with competitive characteristics to be exploited, context that posed the central question ¿How has the productive mining-metallurgical activity of Cu, Zn, Pb influenced the Economic Growth of Peru, 1996-2018? , diligence that provides us with significant economic income, helping to finance higher public spending, favoring to improve the social indicators of poverty, inequality, unsatisfied basic needs, while on the other hand, it has made us more dependent on foreign investment as well as on generating greater environmental impacts. Problematic, which is studied by analyzing what the metallurgical mining activity has implied, in its different and continuous stages, such as investment, production, exports, the same that has contributed to show the Economic Growth of our economy, as a basis for a form of Economic Development.